Colaboração, (ciber)ativismo e subjetividade - Martins, Fernanda Goulart (2013)
This Master Dissertation provides a discussion about subjectivity production, collaborative inventions and cyber activism in neoliberal capitalist and network society. It aims to analyze how subjectivities are built on and configured in the production of discourses on collaborative social spaces in the network society. For this purpose, the research is organized in the form of three articles, intending to (a) construct a methodological pathway that enables an approach to collaborative production, (b) reflect on what collaborative inventions propose in their productions and how they arrange collectively the collaborative inventions and (c) provide a reflection on the knowledge that compose and produce cyber activism. This qualitative research has its reflections based on Critical Social Psychology, but dialogs with other theoretical approaches, such as the phenomenological tradition and hermeneutics, whose epistemological assumptions underpin the reflections developed in the first article, and the philosophy of difference, which provides important concepts for the development of the two following articles. Participant observation and focus groups were proposed as method. This discussions and reflections lead to consider that collaborative productions work and in network and provide resistance and invention processes in search of social transformation.